IMPLEMENTASI SYARAT-SYARAT MUFASSIR DI ERA DIGITAL - Setio Budi (Universitas Islam Malang, 2021)
The mufassir terms are a set of rules or ethics codes for those who want to interpret the content of the Qur'an. These requirements relate to a person's personality and the ruler of scientific disciplines, especially interpretation. The presence of digital technology today makes the study of performance develop so rapidly because the study of understanding is no longer through studies, discussions, halaqah, and recitations in mosques but turns into a digital era. Moreover, this paper explained implementing mufassir requirements in the digital age, whether these conditions be applied in the digital era or are the opposite. In this paper, the writer used descriptive analysis using library data. The results showed that implementing the mufassir requirements in this digital era is the same as the qualifications for the mufassir requirements formulated by scholars in general, plus the ability to be technologically literate, including digital technology.